Upper Bounds for the Hausdorff Dimension of Weierstrass Curves - Alexander, Ted; Murphy, Tommy (The PUMP Journal of Undergraduate Research, 2022)
We produce an upper bound for the Hausdorff dimension of the graph of a Weierstrass-type function. Whilst strictly weaker than existing results, it has the advantage of being directly computable from the theory of hyperbolic iterated function systems (IFS).